Security‐level classification based on power system partitioning. Issue 5 (28th February 2019) - Lu, Zhigang; Zhao, Boxuan; He, Liangce; Zhang, Dan; Zhang, Jiangfeng
Abstract : Secure and reliable operation of power systems is a crucial factor to the security of power supply, and security assessment is an effective way to evaluate the quality of security. In order to evaluate the specific security status of a power system, a novel method for security‐level classification (SLC) based on power system partitioning is proposed here. In this method, power system is partitioned into different subareas satisfying different N ‐ k contingencies. Then, the mutual power supply between each subarea is coordinated to obtain the total supply capacity (TSC) under N‐k contingencies. The security margin (SM) index, average system disequilibrium (ASD) index, and comprehensive safety index (CSI) are applied to assess the security of power system. Besides this, the threshold crossing (TC) index and the loss rate of load (LRL) index are applied to assess the unsafe conditions of power systems. According to the above procedures, the power system security states are classified into five levels, and a quantitative criterion to determine the exact security level is also given. Finally, a practical power system and the IEEE 118‐bus test system are adopted to validate the feasibility of security classification based on N‐k contingencies partition.